Mutagenesis of Wheat Powdery Mildew Reveals a Single Gene Controlling Both NLR and Tandem Kinase-Mediated Immunity - Zoe Bernasconi; Ursin Stirnemann; Matthias Heuberger; Alexandros G. Sotiropoulos; Johannes Graf; Thomas Wicker; Beat Keller; Javier Sánchez-Martín (Molecular Plant-Microbe Interactions, 2024)
Blumeria graminis f. sp. tritici (Bgt) is a globally important fungal wheat pathogen. Some wheat genotypes contain powdery mildew resistance (Pm) genes encoding immune receptors that recognize specific fungal-secreted effector proteins, defined as avirulence (Avr) factors. Identifying Avr factors is vital for understanding the mechanisms, functioning, and durability of wheat resistance. Here, we present AvrXpose, an approach to identify Avr genes in Bgt by generating gain-of-virulence mutants on Pm genes. We first identified six Bgt mutants with gain of virulence on Pm3b and Pm3c. They all had point mutations, deletions or insertions of transposable elements within the corresponding AvrPm3b2/c2 gene or its promoter region. We further selected six mutants on Pm3a, aiming to identify the yet unknown AvrPm3a3 recognized by Pm3a, in addition to the previously described AvrPm3a2/f2. Surprisingly, Pm3a virulence in the obtained mutants was always accompanied by an additional gain of virulence on the unrelated tandem kinase resistance gene WTK4. No virulence toward 11 additional R genes tested was observed, indicating that the gain of virulence was specific for Pm3a and WTK4. Several independently obtained Pm3a-WTK4 mutants have mutations in Bgt-646, a gene encoding a putative, nonsecreted ankyrin repeat-containing protein. Gene expression analysis suggests that Bgt-646 regulates a subset of effector genes. We conclude that Bgt-646 is a common factor required for avirulence on both a specific nucleotide-binding leucine-rich repeat and a WTK immune receptor. Our findings suggest that, beyond effectors, another type of pathogen protein can control the race-specific interaction between powdery mildew and wheat. [Graphic: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.